Genetic variation and recurrent parasitaemia in Peruvian Plasmodium vivax populations - McCollum, Andrea M (BioMed Central, 2014)
BACKGROUND: Plasmodium vivax is a predominant species of malaria in parts of South America and there is increasing resistance to drugs to treat infections by P. vivax. The existence of latent hypnozoites further complicates the ability to classify recurrent infections as treatment failures due to relapse, recrudescence of hyponozoites or re-infections. Antigen loci are putatively under natural selection and may not be an optimal molecular marker to define parasite haplotypes in paired samples. Putatively neutral microsatellite loci, however, offer an assessment of neutral haplotypes. The objective here was to assess the utility of neutral microsatellite loci to reconcile cases of recurrent parasitaemia in Amazonian P. vivax populations in Peru. METHODS: Patient blood samples were collected from three locations in or around Iquitos in the Peruvian Amazon. Five putatively neutral microsatellite loci were characterized from 445 samples to ascertain the within and amongst population variation. A total of 30 day 0 and day of recurrent parasitaemia samples were characterized at microsatellite loci and five polymorphic antigen loci for haplotype classification. RESULTS: The genetic diversity at microsatellite loci was consistent with neutral levels of variation measured in other South American P. vivax populations. Results between antigen and microsatellite loci for the 30 day 0 and day of recurrent parasitaemia samples were the same for 80% of the pairs. The majority of non-concordant results were the result of differing alleles at microsatellite loci. This analysis estimates that 90% of the paired samples with the same microsatellite haplotype are unlikely to be due to a new infection. CONCLUSIONS: A population-level approach was used to yield a better estimate of the probability of a new infection versus relapse or recrudescence of homologous hypnozoites; hypnozoite activation was common for this cohort. Population studies are critical with the evaluation of genetic markers to assess P. vivax biology and epidemiology. The additional demonstration of microsatellite loci as neutral markers capable of distinguishing the origin of the recurrent parasites (new infection or originating from the patient) lends support to their use in assessment of treatment outcomes.